Expansão rápida da maxila assistida por mini implantes e osteotomia maxilar minimamente invasiva - Matje, Paulo Ricardo Baccarin (2020)
Objective: the purpose of this thesis was to present a planning protocol and digital workflow for the application of Minimally Invasive Surgically and Miniscrew Assisted Rapid Palatal Expansion (MISMARPE) technique in adults, using bone-borne expanders, and to quantify skeletal, dentoalveolar and dental changes. Material and Methods: 11 adult patients with transverse maxillary deficiency (mean age 38.1 ± 9.95 years) who underwent MISMARPE technique under local anesthesia in an ambulatory regimen were included. Cone-Beam Computed Tomography (CBCT) were performed at T0 (pre-treatment) and T1 (after the jackscrew activation period). Changes in skeletal, dentoalveolar and dental parameters were assessed using the Paired T-Test. Results: the application of MISMARPE technique produced significant changes in all skeletal and dentoalveolar parameters and in the linear variables of the dental parameters during T0-T1 (p <0.05). There were no significant changes in the angular variables of the dental parameters. Conclusions: the protocol and digital workflow presented allow for ease, security and precision in planning and executing the procedure. The MISMARPE technique can be an effective treatment alternative for the correction of transverse maxillary deficiency in adults, promoting significant skeletal, dentoalveolar and dental changes, however without dental inclinations.